Comparative analysis of Lactobacillus gasseri from Chinese subjects reveals a new species-level taxa - Zhou, Xingya; Yang, Bo; Stanton, Catherine; Ross, R. Paul; Zhao, Jianxin; Zhang, Hao; Chen, Wei (BMC genomics, 2020)
Lactobacillus gasseri as a probiotic has history of safe consumption is prevalent in infants and adults gut microbiota to maintain gut homeostasis. In this study, to explore the genomic diversity and mine potential probiotic characteristics of L. gasseri, 92 strains of L. gasseri were isolated from Chinese human feces and identified based on 16 s rDNA sequencing, after draft genomes sequencing, further average nucleotide identity (ANI) value and phylogenetic analysis reclassified them as L. paragasseri (n = 79) and L. gasseri (n = 13), respectively. Their pan/core-genomes were determined, revealing that L. paragasseri had an open pan-genome. Comparative analysis was carried out to identify genetic features, and the results indicated that 39 strains of L. paragasseri harboured Type II-A CRISPR-Cas system while 12 strains of L. gasseri contained Type I-E and II-A CRISPR-Cas systems. Bacteriocin operons and the number of carbohydrate-active enzymes were significantly different between the two species. This is the first time to study pan/core-genome of L. gasseri and L. paragasseri, and compare their genetic diversity, and all the results provided better understating on genetics of the two species.